Influence of moisture absorption on G(IC) and flexural properties of GRP pipes - R. M Guedes (2010)
In this work the moisture diffusion process and the influence of moisture on mechanical properties (critical strain energy release rate in mode I (G(IC)), flexural modulus and ultimate flexural strength) of GRP pipes was assessed. The research was performed on specimens conditioned in two different environments, water at room temperature and water at 50 degrees C. In this case it was verified that the water diffusion can be well described by the Fick's second law. The critical strain energy release rate in mode I, G(IC), shows a decrease between 5% and 10% when conditioned in water. The temperature of the conditioning does not have so much influence on the G(IC) values. The conditioning either in water at room temperature or at 50 degrees C has an influence on the flexural modulus and strength of the pipes in the hoop direction, between 10% and 20%, respectively. The longitudinal modulus was more significantly affected by the conditioning in water at 50 degrees C with a 30% decrease.